وسائل الإعلام كآلية لتعزيز التنمية من خلال الاشتمال المالي في الدول العربية - عريف, عبد الرزاق (جامعة الوادي - University of Eloued, 2018)
تهدف هذه الورقة البحثية إلى إبراز أهمية وسائل الإعلام في تحقيق التنمية وهذا من خلال تعزيز الشمول المالي على اعتبار أن الاشتمال المالي أحد الأهداف المهمة التي تعمل جميع الدول على تحقيقها في القرن الواحد والعشرين لما له من أهمية في تحقيق التنمية الاجتماعية والاقتصادية فضلا عن مساهمته الكبيرة في تحقيق التنمية المستدامة. كما تهدف إلى تحليل مؤشرات الشمول المالي والتعرف على واقعه في البلدان العربية ومقارنتها ببعضها البعض.The purpose of this paper is to highlight the importance of the media in achieving development by enhancing financial coverage, considering that financial inclusion is one of the important objectives that all countries are working to achieve in the 21st century because of its importance in achieving social and economic development, Achieving sustainable development. It also aims to analyze indicators of financial inclusion and identify its reality in the Arab countries and compare them to each other.
The media as a mechanism to promote development through financial inclusion in Arab countries
مقال
Keywords: الإعلام التنموي، الإعلام الاقتصادي، الاشتمال المالي، مؤشرات الاشتمال المالي،الاستبعاد المالي; Developmental Media, Economic Information, Financial inclusion, financial inclusion indicators, financial exclusion.